Organization Performance Analysis by PM3 Maturity Level in Service Area Field Study PT. GBSI - Karyadi, Karyadi; Rokhmah, Alfiya; Probokusumo, Probokusumo (Eastasouth Institute, 2025)
PT. GBSI is a company that operates in the security services business (outsourcing) and serves its customers based on work contracts per certain period (project), it’s classified in Project Based Organization (PBO) category. Project Management Maturity Model (PM3) is a tool widely used to measure project management performance by looking more broadly at 10 knowledge areas in project management. This research aims to perform an analysis by PM3 maturity level in PT. GBSI. PM3 is used to measure PBO performance in the construction, IT, biotechnology sectors, and currently, it has begun used in service sector, education, and public administration, but there has been no research using PM3 in the provider of security services sector. This research tries to use qualitative approach through interview, document analysis, focus group discussion in diagnosing conditions at PT. GBSI, and use PM3 assessment analysis. The assessment results show the average maturity level achievement in all areas for project management organization is 30% from target maturity level 2. The assessment result can identify the maturity level in the organization and therefore identify development needs in 10 knowledge areas PM3, also provide alternative human processes, technostructure, and human resource interventions to cover the gap maturity level for organizational development.